SEMI–DWARF PRODUCTIVE BARLEY LINES - B. A. Batasheva; V. I. Ibisheva; R. A. Abdullaev; O. N. Kovaleva; I. A. Zveinek; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Resistance to lodging is a factor that significantly affects the yield of barley under the conditions of irrigated agriculture and intensive type of farming. Barley resistance to lodging depends on many features, among which the length of the plant stem is more important.Materials and methods. In the southern planar area of Dagestan, from 1993 till 2008, a research was conducted on the intraspecific diversity of cultivated barley (Hordeum vulgare L.) belonging to different ecogeographic groups, and growth types (2,021 accessions). The F1, F2 and F3 hybrids from crosses of the long-stemmed cultivar ‘Sonet’ with semi-dwarf forms were also studied. The selected recombinant lines were evaluated for their productivity and resistance to frit fly (Oscinella frit L.).Results and conclusions. Wide variability (55–155 cm) of cultivated barley in plant height was observed. Under irrigation in the southern Dagestan, the optimum height of plants, providing high resistance to lodging, was 100–115 cm. A number of semidwarf cultivars were identified; among them, ‘Camincent’ (k-30374, Estonia), ‘Pyramid’ (k-30564, France), ‘Ramos’ (k-30315, Moscow Province) and ‘Jo 1632’ (k-30459, Finland) were the most interesting for their set of traits. The short stem of these cultivars is controlled by recessive alleles of genes. We selected productive lines that significantly exceeded their parental forms in grain weight per area unit and resistance to frit fly: L 15/4 (F6 Sonet × Camincent) and L 16/12 (F6 Sonet × Pyramid). These lines can be used to breed lodging-resistant large-grain barley cultivars for cultivation on irrigated lands.